Pieśń i przypowieść o winnicy (Iz 5,1–7; Mk 12,1–12) - Malina, Artur (Studia Pastoralne, 2026)
The parable of the vineyard (Mk 12,1–12) is an image of God’s dealing with His people. This image is well known form the Old Testament texts, especially from Isaiah’s song (Is 5,1–7). The paper is aimed at investigating the both similarities and differences between the prophetic text and Jesus’ parable. The parallels can be seen in the use of metaphorical language, figures of speech and rhetorical devices. However, Jesus’ parable does not develop in the same way the image present in Isaiah’s song. According to the prophetic text it is the vineyard, which is failed; according to the Gospel the tenants. In Isaiah the vineyard is destroyed, but in the parable it is delivered to new tenants. Isaiah’s message is about God’s punishment of His people, which is definitive; Jesus’ teaching brings hope for God’s salvation in the resurrection of His Son.